Analyse de pratiques, auto-évaluation et normalisation : entre enjeu de professionnalisation et risque de déprofessionnalisation - Richard Wittorski (Questions Vives)
This text intends to analyze the way in which the process of re-standardization of work through the analysis of practices can lead, in a certain number of situations, to produce effects of professionalization of the actors who are engaged in it in the sense that this "work well done" can then be considered as a stabilization and a common formalization of the activity which can be then affirmed by them to facilitate professional recognition in a logic of "professionalization-production of new professionalities". We will also highlight that this process sometimes produces, on the contrary, deprofessionalization effects in the sense that the PA is then accompanied by the development of a habitus of self-evaluation leading the professionals to incorporate the stronger evaluation constraints prescribed by the organization without even being invited to question them in a logic of "professionalization-increase of new professionalism requirements".